ALGERIAN THIRD YEAR ENGLISH COURSEBOOK SCRUTINY: ‘MY BOOK OF ENGLISH’ AS A SAMPLE - Benabed, Ammar; Mehdaoui, Ahmed (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
It is widely acknowledged that coursebooks can be a useful source of information and knowledge for both teachers and learners. They are frequently written by subject-matter experts and can provide a logical and exhaustive overview of the target topic. Referring to the 2022-2023 academic year and with respect to the integration of English in Algerian primary school education, it was noticed that the circumstances in which the decision has been taken might need much more time because the interval between the decision of English integration and coursebook design was too short for a well-thought teaching material. Therefore, the major issue that is being questioned is how well ‘My Book of English’ meets the learners’ age, interest, and attractiveness. The issue under investigation seeks to scrutinize the un/suitability of the current English coursebook content and its impact on 3rd-year primary school learners as regards their competency, needs, and preferences. To answer the research questions and dis/confirm its hypotheses, the study relies on a mixed method, ensuring credible and valid data. Consequently, one questionnaire was put online, and addressed to primary school English teachers, and only fifty-four (54) respondents willingly responded. Besides, the coursebook evaluation grid was filled out by two experts, i.e., primary-school English teachers’ trainers. The results reveal that the coursebook content contains some shortcomings such as poor representation of the language culture, authentic material, grammar logical order, and glossary. In fact, these deficiencies should be palliated for high-quality instruction and successful achievement.